Do types of gadgets used for online learning have a bearing on student academic performance? - Alice Shanthi; Lim Teck Heng; Evelyn Sharminnie; Purwarno Purwarno; Andang Suhendi; Jane Xavierine (Institute of Advanced Engineering and Science, 2023)
This paper explores the impacts of using smartphones vs laptops on students' academic achievement in their English courses and their satisfaction in learning English via open distance learning (ODL). Experiments were conducted in authentic teaching sessions with a total of 304 undergraduates from a local university. The methodology applied is a quasi-experimental design with post-test-only. Results indicate that the relationship between the grade obtained and level of satisfaction with gadget is low and not significant at 5% level of significance. However, there is a significant relationship between the level of satisfaction towards gadgets used for learning English courses and learning English via ODL classes since the p-value is significant with a correlation value of 0.455. Finally, there is a low correlation between the grade obtained and level of satisfaction in learning English during ODL classes. Future research should be conducted to further check on the effects of using mobile phones against other mobile devices on other subjects learnt in the universities.